When bugs were big, plants were strange, and tetrapods stalked the earth : a cartoon prehistory of life before dinosaurs - Bonner, Hannah (National Geographic, 2003)
Takes a tour of the Earth three hundred and twenty million years ago, during the Paleozoic Era, and investigates the plants and animals found there.